Epicentros de instabilidade regional: a política externa da Colômbia e da Venezuela no início do século XXI (2007)
In just a few years, Colombia and Venezuela, two of the most stable democracies in Latin America, changed deeply and are now at the centre of major regional conflicts. The extreme fragmentation and polarization of the political systems in both countries combined with deep social conflicts and the rise of charismatic leaders have created a most volatile environment which has transformed the foreign policies of Colombia and Venezuela and forced them to become regional troublemakers.